IMPLEMENTASI MODUL AJAR DALAM MENINGKATKAN KOMPETENSI SISWA PENDIDIKAN AGAMA KRISTEN DI SEKOLAH SMKS KRISTEN PALANGKA RAYA - Matthew Timothy Palit; Cicha Widia; Adellia Adellia; Santia Oktaviani (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This research aims to examine the implementation of teaching modules in improving student competency in Christian Religious Education subjects at Palangkaraya Christian Vocational School. The teaching modules developed aim to increase students' understanding of teaching materials and facilitate more interactive and effective learning. This research uses a classroom action research (PTK) approach which consists of four stages, namely planning, action, observation and reflection. The research results show that the implementation of teaching modules can increase students' understanding of Christian Religious Education material, as well as increase their learning involvement and motivation. These findings indicate that teaching modules play an important role in improving the quality of learning in the classroom.